Double inferior vena cava with L-type crossed fused renal ectopia: A rare case report - Amita Amita; Samrin Haq; Simmi Bhatnagar; Sugandha Garg; Jasvir Singh (International Journal of Medical Research and Review, 2016)
Duplication of the inferior vena cava (IVC), a rare anomaly reported to occur in 0.2-3% of the population and is known to be associated with various urogenital tract anomalies such as horseshoe kidneys, crossed fused ectopia and circum-aortic renal collar, retroaortic left renal vein and cloacal exstrophy. Inferior vena cava anomalies are rare, Some of such variations have significant clinical, surgical and radiological implications related to other cardiovascular anomalies and in some cases associated with venous thrombosis of lower limbs, particularly in young adults due to the inappropriate venous return increases the pressure, leading to blood stasis in lower extremities and development of varices. Left-sided IVC may cause misdiagnosis with para-aortic lymph node enalargement, and may cause difficulties in the transjugular approach for IVC filter implantation. So, these anomalies should be recognized carefully.